Redox cationic polymerisation - Farrell, David J. (Trinity College (Dublin, Ireland). School of Chemistry, 2011)
The aim of this work is the development of an initiation chemistry that allows preparation of storage stable single-component epoxy compositions, which polymerize when contacted with metallic substrates, at ambient temperatures and without the use of an externally applied energy stimulus such as heat or light. Such epoxy compositions would be considered the cationically initiated analogues of existing radical initiated acrylic systems used commercially as so-called anaerobic machinery adhesives.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.